A systematic review of illness representations in patients with mild traumatic brain injury - Mulyadi, Mulyadi; Tonapa, Santo Imanuel; Amir, Heriyana; Lee, Bih-O (Jurnal Ners, 2023)
Introduction: Little is known about the cognitive and emotional perceptions of patients with mild traumatic brain injury, although studies showed patients experiencing difficulties in cognitive functioning and psychological impacts following their injury. This systematic review aims to identify the current literature regarding illness representation dimensions in mild traumatic brain injury and their related factors. Methods: A search of electronic databases was completed using PubMed, CINAHL, Embase, and Web of Science, which were published from 2002 to April 2020. Studies were assessed for quality and bias, and data were analyzed using narrative synthesis. Results: The initial search yielded 155 studies, and ten were included. The results showed that patients had negative perceptions toward their mild traumatic brain injury. Some dimensions of illness representation were found to have relationships to their post-concussion symptoms, post-traumatic stress disorder, and quality of life of mild traumatic brain injury patients. Conclusions: The illness representations can be applied to such patients because it is able to explain symptoms and related factors that indicate their recovery process. The findings help trauma nurses to build interventions based on the dimensions of illness representations to generate appropriate perceptions after injury, and may to enhance the recovery process and outcomes.